2020
DOI: 10.1302/0301-620x.102b2.bjj-2019-0999.r1
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes of tendon transfer for brachial plexus birth palsy using the Hoffer technique

Abstract: Aims To describe and analyze the mid-term functional outcomes of a large series of patients who underwent the Hoffer procedure for brachial plexus birth palsy (BPBP). Methods All patients who underwent the Hoffer procedure with minimum two-year follow-up were retrospectively reviewed. Active shoulder range of movement (ROM), aggregate modified Mallet classification scores, Hospital for Sick Children Active Movement Scale (AMS) scores, and/or Toronto Test Scores were used to assess functional outcomes. Subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…30,33,35,39,40 in contrast, one study described a statistically significant better mean abduction (6.1 vs 5.2 points, p < 0.001) in the active movement scale, better active abduction ROM (141° vs 118°, p = 0.001), and better Toronto scores (8.8 vs 7.7, p = 0.035) in patients operated at an age younger than 2.5 years, compared to patients operated at an age older than 2.5 years. 28 There was no difference in external rotation between the groups in this study. Finally, the question of whether the indication for secondary surgery should be set in at an early age cannot be answered based on the available literature.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…30,33,35,39,40 in contrast, one study described a statistically significant better mean abduction (6.1 vs 5.2 points, p < 0.001) in the active movement scale, better active abduction ROM (141° vs 118°, p = 0.001), and better Toronto scores (8.8 vs 7.7, p = 0.035) in patients operated at an age younger than 2.5 years, compared to patients operated at an age older than 2.5 years. 28 There was no difference in external rotation between the groups in this study. Finally, the question of whether the indication for secondary surgery should be set in at an early age cannot be answered based on the available literature.…”
Section: Discussionmentioning
confidence: 54%
“…20,31,37,40,42 The mean external rotation improvement ranged between 12° to 72° in the soft-tissue release group, 20,27,31,32,37,42 and between 29° and 128° in the soft-tissue lengthening group. 28,30,33,35,39,43 Since the surgical techniques are different, the groups cannot be compared. One study found preferable results after subscapularis release combined with a latissimus dorsi transfer compared to subscapularis release only.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations